Novel domino procedures for the synthesis of chromene derivatives and their isomerization - Zonouzi, A.; Izakian, Z.; Ng, S.W. (Kluwer (now part of Springer), 2016)
Novel tricyclic keto diesters have been synthesized by a one-pot three-component procedure via DABCO-catalyzed domino Knoevenagel–Michael addition reactions. Also, an efficient four-component reaction for the synthesis of another new group of tricyclic keto diesters has been developed via domino Knoevenagel-intramolecular oxo-Diels–Alder reactions. A selective thermal isomerization of the synthesized chromenes to fumarates is also described. X-ray analyses confirm unambiguously the structures of the products.